Bahasa Ekspresif Melalui Permainan Tradisional Ublek di RA Darul Maza - Sari, Ayu Ratna; Kasih, Delina; Rahayu, Wening (INTELEKTIUM, 2025)
This study aims to improve expressive language skills in early childhood through the traditional game ublek at RA Darul Maza. Language ability is a crucial aspect of early childhood development, influencing social interaction, emotional regulation, and the development of empathy. The research method used is Classroom Action Research (CAR) based on the Kemmis and McTaggart model, conducted in two cycles. Each cycle consists of the stages of planning, action, observation, and reflection. Data were collected through observation, interviews, and documentation. The results showed that consistent and structured implementation of the ublek traditional game can enhance children's expressive language abilities, such as describing textures, expressing feelings, fostering independence, and improving interaction skills. In addition, the activity also supports the development of children's fine motor skills. This study concludes that the traditional game ublek can be an effective strategy to improve expressive language development in early childhood educational settings.